A multi-omic brain gut microbiome signature differs between IBS subjects with different bowel habits. (1st March 2023) - Sarnoff, Rachel P.; Bhatt, Ravi R.; Osadchiy, Vadim; Dong, Tien; Labus, Jennifer S.; Kilpatrick, Lisa A.; Chen, Zixi; Subramanyam, Vishvak; Zhang, Yurui; Ellingson, Benjamin M.; Naliboff, Bruce; Chang, Lin; et al.
Abstract: Alterations of the brain-gut-microbiome system (BGM) have been implicated in the pathophysiology of irritable bowel syndrome (IBS), yet bowel habit-specific alterations have not been elucidated. In this cross-sectional study, we apply a systems biology approach to characterize BGM patterns related to predominant bowel habit. Fecal samples and resting state fMRI were obtained from 102 premenopausal women (36 constipation-predominant IBS (IBS–C), 27 diarrhea-predominant IBS (IBS-D), 39 healthy controls (HCs)). Data integration analysis using latent components (DIABLO) was used to integrate data from the phenome, microbiome, metabolome, and resting-state connectome to predict HCs vs IBS-C vs IBS-D. Bloating and visceral sensitivity, distinguishing IBS from HC, were negatively associated with beneficial microbes and connectivity involving the orbitofrontal cortex. This suggests that gut interactions may generate aberrant central autonomic and descending pain pathways in IBS. The connection between IBS symptom duration, key microbes, and caudate connectivity may provide mechanistic insight to the chronicity of pain in IBS. Compared to IBS-C and HCs, IBS-D had higher levels of many key metabolites including tryptophan and phenylalanine, and increased connectivity between the sensorimotor and default mode networks; thus, suggestingan influence on diarrhea, self-related thoughts, and pain perception in IBS-D ('bottom-up' mechanism). IBS-C's microbiome and metabolome resembled HCs, but IBS-C had increased connectivity in the default mode and salience networks compared to IBS-D, which may indicate importance of visceral signals, suggesting a more 'top-down' BGM pathophysiology. These BGM characteristics highlight possible mechanistic differences for variations in the IBS bowel habit phenome. This article is part of the Special Issue on 'Microbiome & the Brain: Mechanisms & Maladies'. Graphical abstract: Image 1 Highlights: Irritable Bowel Syndrome is a disorder of brain-gut-microbiome interactions. IBS symptom duration and caudate connectivity provide insight into pain chronicity. IBS-C is characterized by abnormalities in sensory processing and emotional regulation. IBS-D is associated with increased gut tryptophan and phenylalanine as well as SMN and DMN connectivity. BGM alterations related to IBS bowel habit subtype were identified with therapeutic implications.